Research Progress of Steel-RAC Composite Structures - Xie, Shu (International Journal of Materials Science and Technology Studies, 2024)
As a new sustainable development technology, recycled aggregate concrete (RAC) has a profound impact on the green development of construction engineering. However, due to the defects of RAC itself, it is hindered in engineering application. The steel-RAC composite structure can effectively enhance the mechanical properties of RAC and promote the application of RAC in practical engineering. Based on the recent research status of steel-RAC composite structures, including recycled aggregate concrete filled steel tube (RACFST) columns and recycled aggregate concrete -encased recycled aggregate concrete filled steel tube (RAC-encased RACFST) composite columns the axial compression, the compression performance, seismic performance and fire resistance of composite columns are reviewed in this paper, and the future research direction is proposed.